2016
DOI: 10.18632/oncotarget.13826
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA RPAIN regulates the invasion and apoptosis of trophoblast cell lines via complement protein C1q

Abstract: Long non-coding RNAs (lncRNAs) are key regulatory molecules that are involved in a variety of biological processes and human diseases. Their impact on early onset preeclampsia remains unclear. In this study, we tested the expression of RPAIN (transcript variant 12 of RPA interacting protein, a non-coding RNA, NR_027683.1) in placenta tissues derived from 25 pregnant women with PE and 15 healthy pregnant women using quantitative real-time PCR. The effect of RPAIN on trophoblast proliferation, invasion, and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 42 publications
(42 reference statements)
1
29
0
Order By: Relevance
“…A recent study has also shown that MEG3’s role in apoptosis and migration may be critical factor in regulating vascular smooth muscle cells during spiral artery remodelling [ 99 ]. Another lncRNA identified as altered in preeclampsia is RPAIN , which by qPCR was shown to be overexpressed in placentas from preeclamptic pregnancies when compared to uncomplicated controls [ 100 ]. Overexpression of RPAIN in HTR8/SVneo cells resulted in inhibition of proliferation and invasion.…”
Section: Lncrnas Are Important For Trophoblast Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has also shown that MEG3’s role in apoptosis and migration may be critical factor in regulating vascular smooth muscle cells during spiral artery remodelling [ 99 ]. Another lncRNA identified as altered in preeclampsia is RPAIN , which by qPCR was shown to be overexpressed in placentas from preeclamptic pregnancies when compared to uncomplicated controls [ 100 ]. Overexpression of RPAIN in HTR8/SVneo cells resulted in inhibition of proliferation and invasion.…”
Section: Lncrnas Are Important For Trophoblast Cell Functionmentioning
confidence: 99%
“…Overexpression of RPAIN in HTR8/SVneo cells resulted in inhibition of proliferation and invasion. The authors went on to show that C1q, a protein that is important for trophoblast invasion and spiral artery remodelling, was also inhibited when RPAIN was overexpressed [ 100 ].…”
Section: Lncrnas Are Important For Trophoblast Cell Functionmentioning
confidence: 99%
“…Our previous study also demonstrated that lncRNA SPRY4-IT1 and MEG3 modulate trophoblast cell proliferation, apoptosis as well as tube formation, invasion and migration in this disorder [14,40,41]. Moreover, other lncRNAs, including ATB, Uc.187, RPAIN and so on, were reported to regulate trophoblast cell growth or/and invasion or/and apoptosis in PE [17,18,42]. Therefore, more and more potential PE-associated lncRNAs need to be identified, the functions of which require further exploration for their underlying biological mechanisms.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, numerous lncRNAs such as RPAIN, MALAT‐1, SPRY4‐IT1, MEG3 and TUG1 have been reported to be abnormally expressed in placentas of PE patients; they may affect the proliferation and metastasis of trophoblast cells, thereby playing functional roles in the pathogenesis of PE. Nevertheless, the underlying mechanisms of these lncRNAs in PE are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%